2021
DOI: 10.1016/j.sjbs.2021.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Are patients affected by chronic non-communicable diseases aware of their own clinical and laboratory parameters? A cross-sectional study from the south of Saudi Arabia

Abstract: Background Patient’s awareness of their clinical and laboratory parameters is an indicator of the degree of involvement in achieving their management goals. This investigation aimed to identify awareness of patients affected by chronic non-communicable diseases of their clinical and laboratory parameters and factors associated with the awareness. Methods This study was a cross-sectional investigation conducted in the Jazan region, between January and August 2020. Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 15 publications
1
11
1
Order By: Relevance
“…Regarding the area of residence, the findings of this study state that the majority of patients were from the city. This finding does not correspond with Reference [26], in which more than half of patients with NCDs from the south of Saudi Arabia were from rural areas.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Regarding the area of residence, the findings of this study state that the majority of patients were from the city. This finding does not correspond with Reference [26], in which more than half of patients with NCDs from the south of Saudi Arabia were from rural areas.…”
Section: Discussioncontrasting
confidence: 90%
“…Regarding patients' educational attainment, the results of this study revealed that one-quarter of patients were illiterate. This finding was supported by Reference [26], in which one-quarter of Saudi patients with chronic NCDs were illiterate. This finding might be because more than one-third of patients in this study were more than 55 years old, and might not have been concerned with education, or might not have been offered opportunities for further education, in the past.…”
Section: Discussionsupporting
confidence: 58%
“…[ 8 ] Additionally, a recent study indicated that patients diagnosed with chronic noncommunicable disease in the Jazan region has limited awareness of their clinical and laboratory parameters, which indicate a low involvement of the patients with achieving management gaols contributing to the control of their conditions and prevention of subsequent ramifications. [ 9 ] Nonetheless, and despite the cumulative evidence, the contribution of PHCs in the prevention of type 2 diabetes in Saudi Arabia is currently not clear.…”
Section: Introductionmentioning
confidence: 99%
“…As per the data obtained from two cross-sectional studies, the average prevalence of hypertension, was found to be 14.8% [27], whereas the awareness, strati ed by the patients' knowledge of SBP and DBP was reported to be 48.7% and 47.3%, respectively [15].The detailed study characteristics are presented in Table 1.…”
Section: Screening Of Studies For Hypertensionmentioning
confidence: 76%
“…Twenty-four studies from structured search were excluded as they did not match the MAPS criteria de nition for patient journey touchpoints. Finally, four studies from the structured searches [10,11,18,19] and 10 studies from the unstructured searches [20][21]22,23,24,25,26,27,28,29] were included in the nal analyses. The literature search and study selection process are presented in Fig.…”
Section: Screening Of Studies For Hypertensionmentioning
confidence: 99%